(untitled) (Research, Society and Development, 2020)
Central ossifying fibroma is a slow-growing, circumscribed, benign and aggressive fibro-bony tumor, known for its expansive growth, the replacement of bone for a fibrous cellular tissue with a focus on mineralization. This lesion occurs in the third or fourth decades of life, with a predilection for females. It affects the mandibule in 70% to 80% of cases. Treatment includes enucleation and curettage or surgical resection for larger lesions. Thus, the aim of this article is to present and evaluate the resources of a clinical case of central ossifying fibroma in the maxilla. Female patient, 34 years old, HIV positive, appear on the service of maxillofacial surgery with painless swelling in the face for months after tooth extraction 12, resulting in feeding difficulties during chewing. On physical examination, diffuse intra and extra-oral edema is evident in the anterior region of the right maxilla, a hardened consistency with 10 months of growth. An incisional biopsy was performed and the material sent for histopathological analysis that concludes of benign bone lesions, suggestive of central ossifying fibroma. The patient underwent enucleation and surgical curettage, under general anesthesia, and was followed-up for 2 years, with no signs of recurrence.